(untitled) (Global Journal of Management and Business Research, 2025)
Procurement compliance plays a vital role in public sector governance by fostering transparency accountability and the effective use of public resources Previous studies have indicated that individual awareness and organizational culture impact compliance behavior however there is limited evidence in Region XII South Cotabato Philippines This quantitative study examined how awareness and organizational culture influence procurement compliance among government agencies in South Cotabato Data were gathered using a structured questionnaire distributed to procurement personnel To analyze the relationships between awareness organizational culture and compliance outcomes descriptive statistics Pearson correlation and multiple linear regression were utilized The findings indicated that both awareness and organizational culture significantly influence procurement compliance A moderate positive correlation was found between awareness and compliance r 0 56 and organizational culture and compliance r 0 59 suggesting that a better understanding and a supportive organizational environment led to improved adherence to procurement regulations To enhance procurement practices it is crucial to raise staff awareness and develop a compliance-focused organizational culture